Bad beliefs : why they happen to good people - Levy, Neil, 1967- (Oxford University Press, 2021)
Bad beliefs - beliefs that blatantly conflict with easily available evidence - are common. Large minorities of people hold that vaccines are dangerous or accept bizarre conspiracy theories, for instance. The prevalence of bad beliefs may be politically and socially important, for instance blocking effective action on climate change. Explaining why people accept bad beliefs and what can be done to make them more responsive to evidence is therefore an important project. A common view is that bad beliefs are largely explained by widespread irrationality. This book argues that ordinary people are rational agents, and their beliefs are the result of their rational response to the evidence they're presented with.